Manajemen Pengembangan Karir Aparatur Sipil Negara (Asn) Berbasis Sistem Merit Di Lingkungan Pemerintah Kabupaten Tulungagung - Agus Setiawan; Arisyahidin Arisyahidin; Deby Santyo Rusandy (Universitas Islam Kadiri, 2023)
This research was done with the aim of knowing how the development management of the country's civil apartment (ASN) was based on a merit system in the government district's Tulungangung.Data source used in observation, library and interview. Using research method approach qualitative analysis, As for the results of this research, the application of the merit system in the Tulungagung district is good. It's proven that the four parts of the agency subjected in this study are almost all qualifications filled with appropriate educational settings. As for some qualified positions that are filled don't fit the educational background because of the appointment of ASN based on an old database.